Enhancing Teachers’ AI Competencies through Artificial Intelligence of Things Professional Development Training - Kitcharoen, Pornchai; Howimanporn, Suppachai; Chookaew, Sasithorn (International Journal of Interactive Mobile Technologies (iJIM), 2024)
The rapid increase in new challenges of the combination of the Internet of Things (IoT) and artificial intelligence (AI), which are emerging technologies, can play a compelling role in prompting the development of artificial intelligence Internet of Things (AIoT). Therefore, the demand for AI competencies for everyone will increase. Educational institutes focus on encouraging AI education because the demand for AI-literate workers will increase in the industrial sector. However, teachers’ lack of AI knowledge is a significant barrier to AI education. Thus, developing the teacher’s AI competencies and educating them about how to use and teach students is critical. In this study, we proposed artificial intelligence of things professional development (AIoT-PD) training to prepare the AI competencies of teachers ready to teach. A quasi-experimental design with a two-day training workshop was conducted among 13 teachers to examine its impact on AI competencies, including AI knowledge, AI skill, and AI attitude. The quantitative data were collected via a pretest and posttest after the training activity, while qualitative data were collected via interviews. This study showed that teachers’ AI knowledge significantly improved. These findings revealed the AIoT training workshop’s effectiveness in enhancing teachers’ AI competencies, which can help them effectively teach students in AI education.